Analysis the Volatiles and Its Aroma Contribution in Rosa Sterilis by HS-SPME and LLE-SAFE - Haoran MO; Mingzheng HUANG; Qun ZHANG; Weiyuan TANG; Tingting LI; Cunbin XU; Xiaozhu LIU; Zhihai YU; Xin LI (Shipin gongye ke-ji, 2023)
To comprehensively analyze the composition and contribution of volatile components in Rosa sterilis, the headspace solid phase microextraction (HS-SPME) and liquid liquid extraction with solvent assisted flavor evaporation (LLE-SAFE) was used, along with gas chromatography-mass spectrometry (GC-MS) to analyze the volatile components. The odor active value (OAV) was used to evaluate the contribution of volatile components to the overall aroma of R. sterilis juice. The results showed that a total of 115 volatile components were identified using both methods, with 59 identified using HS-SPME and 75 identified using LLE-SAFE. These components included 25 esters, 27 alcohols, 11 aldehydes, 14 ketones, 18 acids, 14 terpenes, and 6 other compounds. Analysis of the odor active value (OAV) showed that 30 volatile components, including isoamyl alcohol, 2-hexenal, ethyl hexanoate, ethyl acetate, butyl acetate, hexanal, and hexanoic acid, contributed strongly to the aroma of R. sterilis. This study provides theoretical support for revealing the aroma profile and chemical essence of R. sterilis.